Does esg disclosure and sustainable strategy influence future firm performance? evidence from China's strategic emerging industries - Shenglian, Wang; Azmi, Nurul Azlin; Xiaoyuan, Zhang; Raja Ahmad, Raja Adzrin (GADING Journal for the Social Sciences, 2024)
The rise of the ESG concept has provided new opportunities for firms in strategic emerging industries. The study aims to investigate the relationship between ESG disclosure and future firm performance. A sample of 1,198 firms in strategic emerging industries in China from 2018 to 2022 were analysed inclusively. The Chinese government identified strategic emerging industries as vital for the nation's economic growth and competitiveness in the global market. Additionally, the study examines the regulatory role of sustainable strategy in this relationship since it is pivotal as it incorporates the sustainability agenda into the firm's mission and vision. The study shows that ESG disclosure and sustainable strategy positively influence the future firm performance of strategic emerging industries. This paper expands the research on the mechanism between ESG disclosure and future firm performance. It provides policy inspiration for improving the future firm performance of strategic emerging industries and promoting industrial transformation, upgrading and high-quality economic development.